Role of Adipokines Signaling in the Modulation of T Cells Function - Procaccini, Claudio; De Rosa, Veronica; Galgani, Mario; Carbone, Fortunata; La Rocca, Claudia; Formisano, Luigi; Matarese, Giuseppe (Frontiers in Immunology, 2013)
The field that links immunity and metabolism is rapidly expanding. Apparently non-immunological disorders such as obesity and type 2 diabetes have been linked to immune dysregulation, suggesting that metabolic alterations can be induced by or be consequence of an altered self-immune tolerance. In this context, adipose tissue produces and releases a variety of proinflammatory and anti-inflammatory factors, termed “adipokines”, which can be considered as the bridge between obesity-related exogenous factors, such as nutrition and lifestyle, and the molecular events leading to metabolic syndrome, inflammatory and/or autoimmune conditions. In obesity, increased production of most adipokines impacts on multiple functions such as appetite and energy balance, modulation of immune responses, insulin sensitivity, angiogenesis, blood pressure, lipid metabolism, and so on. This report aims to discuss some of the recent topics of adipocytokine research and their related signaling pathways, that may be of particular importance as could lead to effective therapeutic strategies for obesity-associated diseases.